Circular economy approach to eggshell waste utilisation: Insoluble protein extraction and CaCO3 upcycling for carbonated hydroxyapatite (cHAP)-based fire-resistant wood - Edita Garskaite; Stephen R. Euston; Jozef Martinka; Peter Rantuch; Konrad Wilkens Flecknoe-Brown; Patrick van Hees; Michael Försth; Alexandra Byström; Dietrich Buck; Dick Sandberg (PLoS ONE, 2026)
Transitioning to a resource-efficient and sustainable circular economy is vital for tackling climate- and environmental-related challenges. This study demonstrates a closed-loop strategy for upcycling agricultural biowaste eggshells. Water-insoluble proteins were extracted from both shell membranes and shell fragments by boiling in water using protein denaturants. The ground eggshells also were used to prepare calcium acetate (Ca(CH 3 COO) 2 ) and to treat Scots pine ( Pinus sylvestris L.) sapwood. Mineralisation of the wood was achieved by performing a two-step impregnation process using aqueous solutions of ammonium dihydrogen phosphate (NH 4 H 2 PO 4 ) and Ca(CH 3 COO) 2 salts. Morphological studies revealed the relatively low saturation of wood matrix with mineral, with cell lumina mostly unfilled, while elemental mapping confirmed homogeneous distribution of Ca and P within the wood matrix. Powder X-ray diffraction (XRD) analysis revealed that wood treatment resulted in the in-situ co-precipitation of low-crystallinity hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ), and spectroscopic analysis indicated carbonate substitution within the Ca 10 (PO 4 ) 6 (OH) 2 crystal lattice, suggesting the formation of carbonated hydroxyapatite (Ca 10-x (PO 4 ) 6-x (CO 3 ) x (OH) 2-x-2y (CO 3 ) y ). Microscale combustion calorimeter (MCC) and cone calorimeter (CC) measurements of mineralised wood revealed a reduction in the total heat release (THR) compared with untreated wood, indicating potential for further optimisation of wood modification process. Results suggest that the proposed aqueous solution-based processing approach for converting an abundant resource, chicken eggshells, into value-added products has potential for new technology and bioeconomy development and represents a promising pathway towards improved sustainability.